2004
DOI: 10.1016/j.tca.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

DSC study of precipitation in an Al–Mg–Mn alloy microalloyed with Cu

Abstract: Power compensation DSC has been employed to detect and analyse precipitation reactions in an Al-1.3Mg-0.4Mn and an Al-1.3Mg-0.4Mn-0.07Cu alloy in which very small amounts of precipitate, less than 0.3 at%, are expected to form. Due to the very small heat effects, baseline instability and drift significantly interfere with the measurements. After repeated experiments and careful baseline correction it is demonstrated that in the Cu containing alloy, ageing at 170°C causes the appearance of two endothermic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Bookmark not defined.] and references therein, and references [10,11,13,[15][16][17][18][19][20][21][22]44,51,52,53,65]), and concluded that the present model is consistent with all the available data. In particular it should be noted that no microstructure investigation ever showed evidence for precipitates (other than co-clusters suggested by APFIM, 3DAP) for ageing times within about 10 times the time to reach the plateau hardness (or time to stabilise the enthalpy).…”
Section: Nanostructure Data and Quantum Mechanical Modellingsupporting
confidence: 80%
See 1 more Smart Citation
“…Bookmark not defined.] and references therein, and references [10,11,13,[15][16][17][18][19][20][21][22]44,51,52,53,65]), and concluded that the present model is consistent with all the available data. In particular it should be noted that no microstructure investigation ever showed evidence for precipitates (other than co-clusters suggested by APFIM, 3DAP) for ageing times within about 10 times the time to reach the plateau hardness (or time to stabilise the enthalpy).…”
Section: Nanostructure Data and Quantum Mechanical Modellingsupporting
confidence: 80%
“…Further corrections for imperfections of the DSC as well as correction for the heat capacity contribution not related to reactions of the samples is needed [43]. The optimum choice for this correction is alloy dependent and was considered in [44]. For the Cu-lean alloys 1 and 2, further correction was achieved by subtracting a linear function of T fitted to the initial part of the curve, where no reactions are thought to occur.…”
Section: Methodsmentioning
confidence: 99%
“…The model is limited to considering two precipitates. These are the precipitate responsible for peak strength in Al-Si-Mg based alloys, β″ phase [17,18,19], and the precipitate responsible for peak strength in Al-Cu-Mg based alloys, S phase [15,20,21,22]. In support it is noted that quaternary Al-Mg-Si-Cu precipitates (see e.g.…”
Section: Precipitation Modelmentioning
confidence: 94%
“…To provide an alternative estimate of the magnitude of the heat effect we propose the following semi-quantitative comparisons. Estimates based on a regular solution model outlined in [ 32 ], indicate that about 90% of the Mg present in the Al-1.9Cu-1.6Mg alloy can precipitate as Cu-Mg co-clusters during a DSC run 1 . Then the enthalpy of formation in the Al-1.9Cu-1.6Mg alloy is 14 J/g × 27.5 g/mol/(0.016 × 0.9) = 0.27 eV per Mg atom 2 .…”
Section: The Heat Evolution Due To Cu-mg Co-clustersmentioning
confidence: 99%